2006
DOI: 10.1007/s00425-006-0276-2
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous presence of β-glucuronidase (GUS) in plants and its regulation in some model plants

Abstract: The enzyme beta-glucuronidase (GUS) is well characterized in animals and microbes. However, this enzyme is not well studied in plants and is widely assumed to be absent in them. In this study we document the ubiquitous presence of GUS in the model plants Arabidopsis thaliana, Oryza sativa, Nicotiana tabacum and Zea mays and record its expression pattern. The pH of the assay buffer was found to be critical with pH 4.0 being optimum for detection in all the species. GUS in plants appears to be associated with gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
57
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 50 publications
(48 reference statements)
10
57
0
2
Order By: Relevance
“…The gene uidA codes for β-glucuronidase which is utilized as a reporter in plant genetic transformation because it is generally believed that higher plants do not show GUS-like endogenous activity (Jefferson, 1987;Martin et al 1991;Sudan et al 2006). However, several studies have demonstrated that some plant species show endogenous GUS-like activity in vegetative tissues as well as reproductive organs (Cervera, 2005;Sudan et al 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The gene uidA codes for β-glucuronidase which is utilized as a reporter in plant genetic transformation because it is generally believed that higher plants do not show GUS-like endogenous activity (Jefferson, 1987;Martin et al 1991;Sudan et al 2006). However, several studies have demonstrated that some plant species show endogenous GUS-like activity in vegetative tissues as well as reproductive organs (Cervera, 2005;Sudan et al 2006).…”
mentioning
confidence: 99%
“…However, several studies have demonstrated that some plant species show endogenous GUS-like activity in vegetative tissues as well as reproductive organs (Cervera, 2005;Sudan et al 2006). …”
mentioning
confidence: 99%
“…In different species optimal endogenous GUS-like activity has been reported between pH 4 and pH 6 (Hodal et al 1992), whereas it is histochemically undetectable at pH 7.0 or higher (Alwen et al 1992;Hodal et al 1992;Sudan et al 2006;Solís-Ramos et al 2010a). In contrast, the pH of E. coli-derived GUS has optimum activity at pH 7.0 (Jefferson 1987).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the pH of E. coli-derived GUS has optimum activity at pH 7.0 (Jefferson 1987). Therefore, assaying at this pH for transformation-associated GUS activity, could be a means to discriminate the E. coli-derived GUS from endogenous GUS-like activity (Sudan et al 2006). On the other hand, Kosugi et al (1990) proposed that the use of methanol in GUS buffer eliminated endogenous GUS-like activity, while having no effect or even enhancing the activity of the introduced gusA gene.…”
Section: Resultsmentioning
confidence: 99%
“…Since it has been reported that many legumes exhibit endogenous GUS like activity (Sudan et al 2006), we chose to avoid the use of GUS gene as marker. Instead the FMDV ID gene of the two serotypes "O" and "A 22 " which encodes for major antigenic protein and induces immune response in animals (Meloen and Barteling 1986) was linked together and its expression was used to assess the transformation efficiency.…”
Section: Resultsmentioning
confidence: 99%